Teacher narratives and understandings of (de)humanising pedagogy - Kajee, L. (South African Journal of Higher Education, 2021)
A pre-requisite to teaching and learning for humanisation, is the acknowledgement of our situated selves. Situated selves are positioned in our previous, current, and future experiences. The words we use refer to realities and views of the world (Roux and Becker 2016). For Freire (1993, 68) “to speak a true word is to transform the world”. Education plays a crucial role in transforming people’s worlds, their mindsets, and social relations, that is, in how we name and rename our world. Teachers, therefore, are key mediators of transformative change as agents of social justice, and in the facilitation of learning as transformative specialists (Giroux 1983). Education is therefore a space that would reap the benefits of humanisation. The case study draws on teacher narratives and interviews to explore how teachers understand and reflect on a humanising pedagogy. I conclude that drawing on a humanising pedagogy is a priority for student accomplishment and significant for academic and social resilience.